Effectiveness of case-based learning instruction on pre-service teachers' chemistry motivation and attitudes toward chemistry. Issue 1 (2nd January 2017) - Çam, Aylin; Geban, Ömer
Abstract: Background: The development of primary pre-service teachers' chemistry motivation and attitudes toward chemistry were examined in order to develop their science literacy using case-based learning. Students' ideas were emphasized, real-life situations were discussed, and students could share their ideas and knowledge with peers; as a result, students were active in the learning process. Purpose: The purpose of the study was to investigate the effectiveness of using case-based learning instruction to increase pre-service primary teachers' chemistry motivation and improve their attitudes toward chemistry as a school subject. Sample: The subjects of this study consisted of 51 (20 female, 31 male) freshman primary pre-service teachers from an urban university in Turkey. The mean age of the primary pre-service teachers was 21. Design and methods: One group pre-test and post-test design was used. A chemistry motivation questionnaire and chemistry attitude scale were used for data collection. For the data analysis, two-way repeated measures of ANOVA and repeated measures MANOVA were conducted. Results: The results indicated that the mean of the attitude score after the treatment was significantly greater than the mean of the attitude before the treatment. The results also demonstrated that there is no significant difference between females and males. According to the results of the study, there is no significant difference between primary pre-service teachers' chemistry motivation. However, some chemistry motivation constructs mean scores are greater after the treatment. Conclusions: In sum, it could be stated that case-based learning is helpful for the development of students' chemistry motivation and attitudes toward chemistry.